Domestic water supply - Barnhisel, Clara Florence (My University, 1904)
Introduction: Where ever a large number of people are found, making their home in close proximity to one another, a great amount of water is necessary and a supply of a sufficient quality and quantity becomes a sanitary problem of the greatest importance to every individual in the community. Early in the history of man he recognized the importance of this sanitary problem, and in many an ancient land attempts were made, successfully often, to supply water on a grand scale. In Egypt artificial lakes were made to provide "water where the supply of the Nile proved insufficient. Remains of gigantic water basins have been found in Mexico and Peru. In Ceylon are found the remains of a great artificial tank some forty miles in circumference. But it was in ancient Rome that municipal water supply reached the zenith of its development. At the end of the first century A. D. there were 14 great aqueducts carrying into Rome from the distant mountains some 375 millions of gallons of water daily, or 300 gallons of water per person. During the middle ages all sanitary measures were neglected. At the beginning of the nineteenth century only 17 water works were in existence. During the last century great progress has been made along this line, as well as in other sanitary measures, and at the present time there are in the United States over 4,000 water supplying systems, chiefly owned by municipalities.
Citation: Barnhisel, Clara Florence. Domestic water supply. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Water Supply; Sanitation; Infrastructure; Water Infrastructure; Theses